Kemungkinan Mekanisme Peran Zink dalam Patogenesis Covid-19 - Moch Ikhsan Juliansyah; Lisa Adhia Garina (Jurnal Riset Kedokteran, 2022)
Abstract. This study was conducted to gather sufficient information on the possible mechanism of the role of zinc in the pathogenesis of COVID-19. The method used in this study is a literature study that collects several previous studies to determine the possible mechanism of the role of zinc in the pathogenesis of COVID-19. The results of this study indicate that there are various possible mechanisms of the role of zinc in the pathogenesis of COVID-19 such as preventing virus entry by increasing epithelial integrity, increasing the ability of mucociliary clearance mechanisms, decreasing ACE-2 receptor expression, preventing viral replication by inhibiting RNA polymerase, eliminating viruses by destabilizing them. viral envelope, regulates the immune system such as activation of natural killer cells, cytotoxic T cells, amplifies B cell receptor signaling, antibody formation and regulates regulatory T cell activity and expression of nuclear factor kappa B to maintain a balanced immune response. Thus, it can be said that zinc has a possible role mechanism in the pathogenesis of COVID-19 by preventing the virus from entering, making virus replication, eliminating the virus, and maintaining a balance of immune responses when someone is exposed to COVID-19. Abstrak. Studi ini dilakukan untuk mengumpulkan informasi yang cukup terhadap kemungkinan mekanisme peran zink dalam patogenesis COVID-19. Metode yang digunakan dalam studi ini adalah studi literatur yang mengumpulkan beberapa penelitian terdahulu untuk mengetahui kemungkinan mekanisme peran zink dalam patogenesis COVID-19. Hasil dari studi ini menunjukan adanya berbagai kemungkinan mekanisme peran zink dalam patogenesis COVID-19 seperti mencegah virus masuk dengan meningkatkan integritas epitel, meningkatkan kemampuan mekanisme mucociliar clearance, menurunkan ekspresi reseptor ACE-2, mencegah replikasi virus dengan menghambat RNA polimerasenya, mengeliminasi virus dengan mendestabilisasi envelop virus, meregulasi sistem imun seperti aktivasi sel natural killer, sel T sitotoksik, memperkuat penyinalan reseptor sel B, pembentukan antibodi dan meregulasi aktivitas sel T regulator dan ekspresi nuclear factor kappa B untuk mempertahankan keseimbangan respon imun. Dengan demikian dapat disimpulkan bahwa zink memiliki kemungkinan mekanisme peran dalam patogenesis COVID-19 dengan cara mencegah virus masuk, mencegah replikasi virus, mengeliminasi virus dan menjaga keseimbangan respon imun pada saat seseorang terkena COVID-19.